DICTATIONS AND THEIR TYPES (ResearchJet Journal of Analysis and Inventions, 2021)
This article is about dictation and its types. It provides detailed information on the types of dictations. Here's a few basic facts about a stomp pad and how it is used. It explains the purpose of dictation from elementary school students.